Usage of Reference Management Software by Postgraduate Students at the University of Dar es Salaam, Tanzania - Mhokole, Erick Leonard; Kimaryo, Collin (University of Dar es Salaam Library Journal, 2023)
This paper presents the of a study conducted at the University of Dar es Salaam (UDSM), Tanzania on the usage of Reference Management Software (RMS) by postgraduate students and guided by TAM and DIT theories. The study employed a descriptive research design and collected both quantitative and qualitative data. It also used stratified and simple random sampling techniques to draw samples. One hundred and four (104) respondents participated in this study. The study used questionnaire and documentary review methods to collect data. Key findings revealed that a majority of the respondents are aware of RMS. The most commonly known RMS is Mendeley. Findings further revealed that most respondents have a favourable attitude toward RMS and perceive RMS as useful and easy to use, even though few actually use RMS mainly to write research proposals and theses/dissertations. The study also revealed that postgraduate students encounter challenges in using RMS including inadequate requisite skills, lack of technical services support, lack of internet connectivity and unreliable power supply. The study concluded that the usage of RMS by postgraduate students at UDSM is low.